PHYSICO-CHEMICAL AND PHYTOCHEMICAL SCREENING OF n-HEXANE EXTRACT OF LEPTADENIA HASTATA LEAVES: A PROPOSED HERBAL REMEDY IN THE TREATMENT OF DIABETES MELLITUS - M.O.O, Attah; T.W, Jacks; S.H., Garba; H.E., Mshelia (International Journal of Research -GRANTHAALAYAH, 2019)
Background: Leptadenia hastata is a leafy, climbing plant of whose root, leaf and bark is widely consumed in Northern Nigeria. Decoctions made from the leaf is locally used in treatment of diabetes as well as for numerous trado-medicinal processes. This study investigates the physico-chemical as well as phytochemical compounds present in the n-hexane extract of Leptadenia hastata. Method: Physical and chemical profile was determined using Smart Spectro test kits and a mass spectrometer to determine the presence of elements and physical properties. Results: Phytochemical analysis revealed the presence of steroids, triterpenoids and cardiac glycosides. The elemental analysis revealed that Na, SO4 and PO4 had the highest levels in the extract. Pb, Hg and Cd were not detected which showed that the plant extract was not toxic. Other elements (NO4, Mn, Fe, K, Ni, Si, Cn, Zn, Ca, Mg, NH4, Cr and F) were present in varying concentrations which may contribute to its nutritive composition. Conclusions: Various elements present in Leptadenia hastata may have either a direct or indirect role in the control and management of diabetes mellitus, since diabetes is associated with marked alterations in trace elements concentrations and may replace diminished element stores in the treatment of diabetes mellitus.